Newsletter No. 18 - (:unkn) unknown (My University, 2007)
Information about the LSAC Research Conference and Data Training, how Wave 3 is progressing, Wave 2.5 between waves contact, and the 'Life at' series is in the Spring Newsletter, as well as recent publications and conference presentations using Growing Up in Australia data.
18
Newsletter
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology